The porous mask: a theological reflection on concepts of personhood and personal agency in the digital age - Höhne, Florian (Cursor_, 2022)
Given the metaphorical and technical transitions between machines and people, what is a person? Drawing on John Locke and Dietrich Bonhoeffer, Florian Höhne reflects on imaginations and practices of the digital juxtaposing a forensic imagination of personhood with a responsorial imagination of personhood, respectively, and discusses their implications regarding digital transformations.